Stachys cudiensis (Lamiaceae), a new species from Şırnak province (Turkey), belonging to section Olisia - Firat, Mehmet; Güner, Özal (Phytotaxa, 2022)
A new species, Stachys cudiensis (section Olisa), is described and illustrated from Şırnak province, Turkey. The new species morphologically resembles Stachys diversifolia, but differs in several morphological features including retrorsely pubescent flowering stems, oblong to oblong-lanceolate bracteoles, short calyx with densely glandular hairs and sessile glands and gibbous corolla tube and nutlet dimensions and surface properties and prolate-spheroidal pollen shape. A comprehensive description of the new species micromorphological and palynological data are provided, including detailed photographs, geographical distribution map, habitat structure and ecology, vernacular name and IUCN conservation status.